Die politieke dimensie in die romankuns van André P. Brink: 'n Etiese evaluering - Wyk, J. H. van (Koers, 1986)
The author justifies writing about the political dimension in the novels of André P. Brink on the basis that committed literature also embraces the political dimension as one of its m any dimensions. He thus proposes to deal not with whether but how this dimension manifests its e lf in the literature. A rising line of political involvement is detected in the late st novels - and this tendency can be defined in terms of "in situation alized violence ". An analysis of a number of novels, including Kennis van die aand, Houd-den-bek and Muur van die Pes underscores his views, and reveals, too, a view that the church is caught up in pietistic immobility, and that the novels abound in Existentia list, Marxist and even at times Calvin is ethical motifs. The political dimension is then evaluated in terms of Calvin is views and the Calvin is tradition - especially in view of the concept of the justifiability of violence and in surreciton.